Análisis del Proceso de Contratación Pública en la Gestión Administrativa del GAD Municipal del Cantón Zamora, año 2024 - Cueva Cueva, Yomaira Mercedes (2024)
The present research work includes an analysis of the public procurement processes in the administrative management of the Municipal GAD of the Zamora Canton, year 2024 within what governs the Constitution of the Republic and the Organic Law of the National Public Procurement System (LOSNCP) a qualitative approach methodology was used to understand in a clear and detailed manner through interviews relevant information about public procurement processes to public servants in the public procurement area and suppliers, and an analysis of the procurement records carried out. . within the study period. The results reveal that, although significant progress has been made in the implementation of contractual procedures, challenges persist in the effective execution of the PAC, such as insufficient budget execution and the lack of rigorous monitoring in some processes. Additionally, the need to improve transparency and efficiency in the management of public resources is identified by adopting good practices and implementing an internal control system to optimize processes, costs and threats of irregularities, as well as adopting modern international standards that can help the quality of hiring without errors. Finally, it is proposed to strengthen the management of public procurement in the Municipal GAD of Zamora, which includes the constant training of staff, the implementation of advanced technological systems for the management of procurement and its control that allow errors to be detected or corrected, among others. These proposals seek not only to increase the efficiency and effectiveness of contractual processes, but also to promote trust in citizens and the active participation of suppliers in public procurement processes.